Chromosomal relationships of Simulium armoricanum and its undescribed sister species in the Simulium vernum species group (Diptera: Simuliidae) - Adler, Peter H.; Belqat, Boutaïna; González, Josefina Garrido; Pérez, Alexandre Justo; Seitz, Gunther (Zootaxa, 2016)
The banding sequence of the polytene chromosomes of Simulium armoricanum Doby & David from England, Portugal, and Spain was resolved relative to the standard map for the S. vernum group. The species is characterized by 11 fixed inversions, one nearly fixed inversion, and three common polymorphisms. The sister species of S. armoricanum is proposed as a formally undescribed species discovered in samples from Portugal. It shares one unique inversion with S. armoricanum, but otherwise differs by eight fixed or nearly fixed rearrangements. Simulium armoricanum and its newly discovered sister species, informally referred to as Simulium ‘IL-8’, are members of a larger clade of Palearctic species defined by a small pericentric inversion in chromosome III. Among the simuliid species occupying the same streams with S. armoricanum was the first record, chromosomally confirmed, of S. aureum Fries sensu stricto in Portugal. Successful chromosomal analysis of samples of S. armoricanum 17 years after initial fixation demonstrates the importance of storing cytologically fixed larvae at subzero temperatures.